Global Trade Pattern of Medical Devices and China's Trade Position: Based on Data From 2001 to 2020 - Hao Hu; Xiaoping Wang; Haiyan Zhou; Zhuang Jin; Shaobin Wei (Frontiers in Public Health, 2022)
To depict the evolution of the global trade of medical devices, this study analyzes the spatiotemporal evolution characteristics of global and China's trade patterns of medical devices from 2001 to 2020 based on data from the World Bank and United Nations Commodity Trade Statistics Database, and thereby investigates the status quo of global and China's medical device trade, as well as changes in China's position in the global medical device trade. The findings are as follows. First, the total global trade volume of medical devices is generally on the rise, showing closer network connections. Despite some changes in trade position, the core countries in the global medical device trade network are relatively fixed. The intermediate position of core trading countries has been weakened on the whole, whereas exporting countries have generally assumed an enhanced central position. Communities with geographical proximity have been formed in the global medical device trade network, including two large communities, the Asian-European countries and the Pacific Rim countries, and one small community, the South American countries. Second, with its rapidly growing trade volume of medical devices with other countries, China has now become the fourth largest medical device trading country in the world. Its number of import and export partners has remained relatively stable and continued to increase. Its export markets are relatively concentrated, and a tripartite pattern of import sources has been formed. China has established extensive interdependent relations and almost no one-way dependent relations in the medical device trade. Among its major trading partners for medical devices, the interdependence of China with developed countries/regions, such as European and American countries and Japan, has generally deepened.